2022
DOI: 10.1039/d2tb01414a
|View full text |Cite
|
Sign up to set email alerts
|

A bivalent aptamer and terminus-free siRNA junction nanostructure for targeted gene silencing in cancer cells

Abstract: Small interfering RNA (siRNA) has increasingly evolved as a potent therapeutic solution for several pathological conditions including cancers via post-transcriptional oncogene suppression in cellular pathways. And, the key for siRNA-based...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…Camorani S et al [27] coupled aptamers with siRNA targeting programmed cell death ligand 1 (PD-L1) to achieve effective gene silencing in triple-negative breast cancer. Fang Yang et al [28] developed a self-assembled structure of bivalent aptamer and terminal-free siRNA, which was easy to prepare and effective in inducing apoptosis. The coupling of nucleic acid aptamer and siRNA shows potential in the field of tumor-targeted therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Camorani S et al [27] coupled aptamers with siRNA targeting programmed cell death ligand 1 (PD-L1) to achieve effective gene silencing in triple-negative breast cancer. Fang Yang et al [28] developed a self-assembled structure of bivalent aptamer and terminal-free siRNA, which was easy to prepare and effective in inducing apoptosis. The coupling of nucleic acid aptamer and siRNA shows potential in the field of tumor-targeted therapy.…”
Section: Discussionmentioning
confidence: 99%
“…On this basis, numerous related methods based on DNA nanotechnology have been reported over the past years. [125][126][127][128] For instance, Shin's group designed diversified rectangular and tubular DNA nanostructures of different dimensions and shapes by the modularized DNA brick approach, which enabled high-efficiency transport of siRNA targeting the Bcl2 protein with anti-apoptosis function. 125 The experimental results showed that DNA nanoparticles had high endocytosis efficiency; the loaded siBcl2 could down-regulate the Bcl2 expression by about 90% and silence Bcl2 mRNA by about 70%, subsequently inhibiting cell growth.…”
Section: Therapeutic Nucleic Acid Delivery and Disease Treatmentmentioning
confidence: 99%